Immune checkpoint blockade in hepatocellular carcinoma: Current progress and future directions - Hato, Tai (2014)
Immune checkpoint blockade has recently emerged as a promising therapeutic approach for various malignancies including hepatocellular carcinoma (HCC). Preclinical and clinical studies have shown the potential benefit of modulating immunogenicity of HCC. In addition, recent advances in tumor immunology have broadened our understanding of the complex mechanism of immune evasion. In this review, we summarize the current knowledge on HCC immunology, and discuss the potential of immune checkpoint blockade as a novel HCC therapy from the basic, translational, and clinical perspectives.